Application Cow Manure and Mychorriza to Physiological of Biduri (Calotropis gigantea) - Sri Hartati; Samanhudi Samanhudi; Muji Rahayu; Mochammad Danny Sukardan; Nadia Alifia Rahma (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2022)
Biduri (Calotropis gigantea) was a wild plant that had many benefits in the health and textile industries. In the health sector, biduri was used as a herbal plant, while in the textile industry, used as the main raw material. Biduri could be used as a substitute for kapok as the main raw material, therefore it was necessary to develop cultivation technology to met the needs. This research was conducted at the Jumantono Field Laboratory of Faculty of Agriculture UNS, Karanganyar using a factorial Randomized Complete Block Design (RCBD), which consisted of 2 factors, namely cow dung fertilizer, and mycorrhizae. Cow dung fertilizer consists of 0 ton/ha, 10 ton/ha, and 20 ton/ha. Mycorrhizae consisted of 0 grams/plant, 5 grams/plant, 10gram/plant, and 15gram/plant. There were 36 treatment combination that consist of 12 treatment combination repeated 3 times. The interaction between cow dung did not significantly affect all physiological observation variables. The results showed that the application of 20 ton/ha of cow dung fertilizer gave the best results on the width of stomata openings, the rate of photosynthesis, and the rate of transpiration. Inoculation with mycorrhizal fungi had no significant effect on all observations of physiological variables Keywords: Calotropis gigantea, cow manure, mycorrhiza, physiological